Running critical power: between-day, interlimb and interunit reliability - Ruiz-Alias, S. A.; Ñancupil-Andrade, A. A.; Pérez-Castilla, A.; Garcia-Pinillos, F. (Sports Engineering, 2024)
This study aims to determine the between-day, interlimb and interunit reliability of the running critical power and work over it derived from the power outputs reported by a commercial power meter. Fifteen highly trained long-distance track athletes (8 males and 7 females; 5000 m season-best: 15:29 ± 00:53 mm:ss) performed two testing sessions composed of a 9- and 3-min time trial interspaced by 30-min. The critical power and work over it were obtained from the linear inverse of time critical power model. To determine the between-day reliability, athletes wore the power meter on the right footwear in the first and second testing sessions. To determine the interlimb reliability, athletes wore two units on the left and right footwear in the second testing session. To determine the interunit reliability, two units were placed on the left footwear in the second testing session. The results revealed that for determining a meaningful change in performance through the power meter, practitioners should consider those changes in critical power and work over it exceeding 4% and 10%, respectively. Similar magnitudes were required to consider between lower limbs (i.e., critical power: 4%; work over critical power: 11%) and between units (i.e., critical power: 3%; work over critical power: 10%). In conclusion, practitioners should consider these values when using the commercial power meter to interpret meaningful changes in performance and asymmetries between lower limbs.